2017
DOI: 10.1088/1361-6587/aa72a3
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of machine-learning-based disruption models for plasma control

Abstract: While machine learning techniques have been applied within the context of fusion for predicting plasma disruptions in tokamaks, they are typically interpreted with a simple 'yes/no' prediction or perhaps a probability forecast. These techniques take input signals, which could be real-time signals from machine diagnostics, to make a prediction of whether a transient event will occur. A major criticism of these methods is that, due to the nature of machine learning, there is no clear correlation between the inpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, these algorithms are often trained and tested on limited datasets from a single tokamak, and few cross-machine comparison studies have been implemented [11,12]. The methods typically used in previous work have also generally relied on black-box ML algorithms, which have few methods available to interpret their predictions [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, these algorithms are often trained and tested on limited datasets from a single tokamak, and few cross-machine comparison studies have been implemented [11,12]. The methods typically used in previous work have also generally relied on black-box ML algorithms, which have few methods available to interpret their predictions [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these estimates should be considered as a preliminary measures of signal importance. It must be noted that a method has been proposed to determine how sensitive the state of a plasma is at any given time with respect to the input signals [28]. It is demonstrated that the normalized gradients function is a key factor for the disruption as it can describe the sensitivity of the parameter to the features of disruption.…”
Section: Performance Of Disruption Prediction Modelmentioning
confidence: 99%
“…(v) Finally, the linear extrapolation of disruptivity employed in this paper is quite simple (even crude), especially considering that plasma parameters can be actuated in real time to navigate in "disruptivity space." A smarter method, such as that described in [36], could be used to calculate gradients in parameter space and map possible trajectories away from the disruptive boundary (P D = 1, in this case). Furthermore, dynamical models of the the plasma state vector x(t)-which is input into the disruption predictor, i.e.…”
Section: Opportunities For Future Workmentioning
confidence: 99%